RISK MANAGEMENT ANALYSIS ON THE PIER REPAIR CONSTRUCTION PROJECT AT PT. ORELA SHIPYARD GRESIK - Priyo Bagus Bowoleksono; Rizal Bahaswan (E-Jurnal SPIRIT PRO PATRIA, 2025)
This study aims to analyze risk management in the pier repair construction project at PT Orela Shipyard Gresik. Through the risk identification and assessment stage, the study identified twenty-five indicators out of a total of thirty-seven relevant, which were grouped into six main categories: project risk, technical, natural, human, occupational safety and health (OHS), and financial. The results of the analysis show that technical risk is the most dominant, followed by project and financial risk. This study also conducted a validity and reliability test on the measurement instruments used, with results showing that all indicators are valid and realistic. Recommendations for mitigation actions are given to reduce the negative impact of the risks, in order to ensure the smooth implementation of the project.